2013
DOI: 10.1177/1757913912466946
|View full text |Cite
|
Sign up to set email alerts
|

The effects of participating in creative activities on the health and well-being of children and young people: a rapid review of the literature

Abstract: Although the research evidence is generally weak there is some evidence that using creative activities as part of a health-promoting strategy may be a useful method of increasing knowledge and positive behaviours in children and young people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
84
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 145 publications
(98 citation statements)
references
References 22 publications
8
84
0
6
Order By: Relevance
“…These are all factors that are important conditions for developing empowerment (Askheim, 2003). These findings are also in accordance with findings reported by Bungay and Vella-Burrows (2013), Kemp (2006), andMohler (2012). Kemp (2006) reports that participating in theatrical activities promotes young people's self-esteem and a positive sense of agency and thus creates opportunities for self-expression, reflection, and self-understanding.…”
Section: Inclusive Theatre As Contribution To Empowermentsupporting
confidence: 80%
See 1 more Smart Citation
“…These are all factors that are important conditions for developing empowerment (Askheim, 2003). These findings are also in accordance with findings reported by Bungay and Vella-Burrows (2013), Kemp (2006), andMohler (2012). Kemp (2006) reports that participating in theatrical activities promotes young people's self-esteem and a positive sense of agency and thus creates opportunities for self-expression, reflection, and self-understanding.…”
Section: Inclusive Theatre As Contribution To Empowermentsupporting
confidence: 80%
“…A literature review by Bungay and Vella-Burrows (2013) has found that a number of the studies reported on projects which were introduced with the purpose of helping to build communities and to increase social engagement. Creative activities have also been used to promote behavioural change and healthy lifestyles.…”
Section: Theatre and Creative Arts In Work With Young Peoplementioning
confidence: 99%
“…Participating in creative arts has been linked to positive outcomes for children and young people such as the development of social skills and positive changes in behaviour [1]. Within the UK there are a number of organisations providing programmes of arts activities for children and young people (for example Arts and Minds (www.artsandminds.org.uk), and Start Youth Arts (www.startinsalford.org.uk).…”
Section: Introductionmentioning
confidence: 99%
“…A review exploring the effects of participating in creative activities on health and wellbeing of children and young people found that increased self-esteem, sense of achievement, empowerment, social skills, promotion of social engagement are some of the commonly reported benefits of taking part in such activities [1].…”
Section: Introductionmentioning
confidence: 99%
“…Na literatura internacional, há estudos relacionando atividades extracurriculares com aumento de saúde e bem-estar (Bungay & Vella-Burrows, 2013), melhoria de desempenho acadêmico, assim como de habilidades não-cognitivas (Covay & Carbonaro, 2010) e com a preocupação em não deixar crianças sozinhas em casa (Larner, Zippiroli, & Behrman, 1999). Covay & Carbonaro (2010) correlacionam a participação em atividades extracurriculares com questões socioeconômicas, sendo que crianças de classes sociais média/alta participam de um número maior de atividades quando comparadas a crianças de classes pobres.…”
Section: Fundamentação Teóricaunclassified